Energetic and exergetic analysis of solar-powered lithium bromide-water absorption cooling system. (10th May 2017) - Kerme, Esa Dube; Chafidz, Achmad; Agboola, O. Philips; Orfi, Jamel; Fakeeha, Anis H.; Al-Fatesh, Ahmed S.
Abstract: This paper presents a comprehensive thermodynamic modeling of the solar-powered lithium bromide -water (LiBr-H2 O) absorption chiller system. The study examined the influence of the solar collector types on the collector efficiency and the useful heat gain by the collector for the best performance. The study also analyzed the effects of generator inlet temperature, effectiveness of the solution heat exchanger and the pump mass flow rate on the energetic and exergetic performance of the chiller system. The examined performance parameters were coefficient of performance, exergetic efficiency, exergy destruction, fuel depletion ratio and improvement potential. The study revealed that 'evacuated selective surface' collector type has resulted in higher efficiency and more useful heat gain than the single and double glazed collector types. Additionally, the increase in the heat exchanger effectiveness improved the system performance, while the increase in the pump mass flow rate reduced the chiller performance. Furthermore, the result also indicated that the main source of the exergy destruction is the solar collector. In the solar collector, 71.9% of the input exergy was destroyed which accounted for 84% of the total exergy loss. Additionally, 7.1% of the inlet exergy was lost in the generator which was equivalent to 8.3% of the total exergy loss. The overall exergetic improvement potential of the system was approximately 84.7%. Graphical abstract: Highlights: Energetic and exergetic analysis of solar-driven absorption cooling were studied. Effect of inlet temperature on energetic and exergetic performance was examined. Effect of collector types on efficiency and useful heat gain was investigated. Overall exergetic improvement potential of the system was evaluated. Solar collector is the main source of exergy destruction.